2010
DOI: 10.1007/s11999-009-0977-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Arm-assisted UKA Improves Tibial Component Alignment: A Pilot Study

Abstract: The alignment of the components of unicompartmental knee arthroplasty (UKA) reportedly influences outcomes and durability. A novel robotic arm technology has been developed with the expectation that it could improve the accuracy of bone preparation in UKA. During the study period, we compared the postoperative radiographic alignment of the tibial component with the preoperatively planned position in 31 knees in 31 consecutive patients undergoing UKA using robotic arm-assisted bone preparation and in 27 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
117
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 9 publications
7
117
0
4
Order By: Relevance
“…The jigs used in this study only carefully directed the vertical cut rather than rigidly guide it. But more importantly, the bony anatomy of lateral aspect of the medial condyle may actually guide this cut more than any other structure and thus determine the [19]. Seon et al gave their results for coronal tibial alignment using navigation in UKA [25].…”
Section: Discussionmentioning
confidence: 99%
“…The jigs used in this study only carefully directed the vertical cut rather than rigidly guide it. But more importantly, the bony anatomy of lateral aspect of the medial condyle may actually guide this cut more than any other structure and thus determine the [19]. Seon et al gave their results for coronal tibial alignment using navigation in UKA [25].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic assistance enhances the accuracy of bone preparation, implant component alignment, and soft tissue balance in unicompartmental knee arthroplasty (UKA) [1][2][3][4][5][6]. Such precision relies on patient-specific preoperative and/or intraoperative mapping, which depending on the system utilized, may require a three-dimensional computed topography (CT) scan of the involved knee and ipsilateral hip and ankle.…”
mentioning
confidence: 99%
“…Song et al [28] reported that the mean operation time was 25 minutes longer for robot-assisted TKA compared to the conventional method, but that there was no increase in short-term complication rates. A high complication rate was reported in early cases of robot-assisted surgery, including bone pain related to the implanted fiducials and the fixation jig [19,22,30]. Park and Lee [22] found that complaints about these problems seemed to be lessened after switching to smaller fixation markers and jigs, and no major adverse results have been observed following completion of the learning process.…”
Section: Discussionmentioning
confidence: 99%